The summons [Sudca anglicky] - Grisham, John, 1955- (Fiction, 2007)
Knowing that the end is near, Judge Atlee has issued a summons for his two sons to return to Clanton to discuss his estate. Ray Atlee is the elder, a Virginia law professor, newly single, still enduring the aftershocks of a surprise divorce. Forrest is Ray’s younger brother, the family’s black sheep.The summons is typed by the Judge himself, on his handsome old stationery, and gives the date and time for Ray and Forrest to appear in his study. Ray reluctantly heads south to his hometown, to the place he now prefers to avoid. But the family meeting does not take place. The Judge dies too soon, and in doing so leaves behind a shocking secret known only to Ray . . . and perhaps to someone else.